An analysis of English Materials for Effective Communication as Tour Guides - Supartini, Ni Luh; Susanti, Luh Eka; Koeswiryono, Dika Pranadwipa (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2024)
Effective speaking skills are essential for a tour guide to provide a satisfying experience to international tourists. This research is an effort to meet the need for teaching materials for English speaking skills that are suitable for tour guides. This research uses the Research & Development method which is carried out in three stages; namely the exploration stage, prototype development stage, and expert validation stage. Data was collected through in-depth interviews, document analysis, and expert assessment. The data was then analyzed using descriptive-qualitative and interactive analysis. The research results show that English teaching materials for tour guides are really needed. The materials required include daily conversation, focus on speaking skills, an informal class atmosphere, and no homework. Meanwhile, at the principle stage, the guideline for preparing English language skills teaching materials is that this approach must be student-centered. Tour guides' intrinsic motivation needs to be taken into account, materials should provide input that is comprehensible but also challenging, recycling of target language knowledge needs to be done regularly Lastly, the importance of teaching intercultural competence cannot be ignored, preparing tour guides to communicate with tourists from various backgrounds culture. These findings recommend that English language materials for tour guides be implemented immediately to provide excellent service to international tourists.